ASSESSMENT OF THE IMPACT OF EDUCATION-RELATED FACTORS OF INTELLECTUAL CAPITAL ON ENSURING THE STABILITY AND SECURITY OF THE ENTREPRENEURIAL SYSTEM - Yuldashbayev, Azizullokh (THE INNOVATION ECONOMY, 2026)
In the context of innovation, the issue of statistical analysis of indicators of employees’ knowledge level and qualifications, which reflect the characteristics of intellectual capital as the main type of human factor in the development of the entrepreneurship system, has been studied.